An introduction to veterinary immunology: innate immunity - Tizard, Ian (Henry Stewart Talks, 2020)
Characteristics of innate immunity, Triggers of innate immunity, The involvement of innate immunity in inflammation, Cells of the immune system, Innate immunity and inflammation do not improve over time